Organizational Commitments of Government Officers in Department of Health Service Support, Ministry of Public Health, Thailand - Chujarearnpipat, Sujintra; Intaraprasong, Bhusits; Sillabutra, Jutatip; Sattayasomboon, Youwanuch (Journal of Health Science of Thailand, 2018)
This research was an explanatory research whose objective was to find the relationship of organi-zational climate with organizational commitment of government officers in Department of Health Service Support, Ministry of Public Health, Thailand. The sample group was 250 partipants composed of civil servant, government employee and permanent employee who had been working in Department of Health Service Support in the central for not less than one 1 year and non-administrative positions. Data was collected by using a questionnaire. Statistical analysis of the data was performed by using descriptive statistics, Pearson’s product moment correlation coefficient and multiple regression analysis. The results revealed that government officers in Department of Health Service Support had a low level of organiza-tional commitments. The Department had a very good level of organizational climate. Organizational climate had a medium level positive association with organizational commitment. The organizational cli-mate with work organization had most association; followed by relations, cooperation, participation, at-tachment to the job and innovation, respectively. The organizational climate could explain 49.60% (R 2 =0.496, p<0.001) of the variation of organizational commitment among personnel of the Department of Health Service Support. According to the results of the research, the Department of Health Service Support administrators should promote and enhance organizational commitment and organizational climate within the organization. In addition, the Department should provide opportunity for people to participate in thinking and planning creation of works promotion of progress and strengthen communication within the organization.